In situ fabrication of constraints for multicellular micro-spheroids using two-photon lithography - Taale, Mohammadreza; Schamberger, Barbara; Taheri, Fereydoon; Antonelli, Yasmin; Leal-Egaña, Aldo; Selhuber-Unkel, Christine (Advanced functional materials, 2023)
2-photon polymerization is a promising technology for creating complex, microscale 3D matrices for biomedical and also bioprinting applications. Cancer research provides compelling uses for this strategy, in particular, for generating a 3D constraint around multicellular spheroids. Because these spheroids are inhomogeneous in size and shape, the ability to target a spheroid composed of a few living cells requires geometrical control of the printing shape in situ. In this study, it is presented that two-photon lithography can be used to study complex phenomena involved in cancer progression, such as collective 3D cell migration in situ in vitro. This method allows the spatial and temporal control of cancer cell migration from single spheroids, using dome-shaped confinements with micrometer-sized openings. The confinement of the spheroids leads to a decreased migration speed and affects actin dynamics. Furthermore, this methodology provides a novel way of analyzing the behavior of specific regions of multicellular structures, by enabling the separation of multicellular structures, while keeping them alive. Ultimately, this study demonstrates a new way to use two-photon lithography for controlling the growth, migration and morphological cues of live cells, thus opening new avenues toward the dynamic in situ control of living 3D structures.
Gesehen am 21.02.2024